Matilda - Dahl, Roald 1916-1990 (Penguin Audio, 2013)
Matilda is an exceptional five-year-old who's a whiz at reading and multiplication. However, her life is far from perfect. She has two of the most idiotic, self-centered parents who ever lived. Matilda uses her intelligence to get revenge on her father, but her skills are put to the test by her horrible nightmare of a principle, Mrs. Trunchbull
Compact discs
Title from disc label
Keywords: Wunderkind; Gifted children / Juvenile fiction; Child abuse / Juvenile fiction; Parent and child / Juvenile fiction; Gifted children / Fiction; Child abuse / Fiction; Parent and child / Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / School & Education; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; Child abuse; Gifted children; Parent and child; Audiobooks; Children's; Children's audiobooks; Fiction; Juvenile works; Humorous fiction; Hörbuch; Kinderbuch; CD